Quality Evaluation of Decoction Pieces of Gardeniae Fructus Based on Qualitative Analysis of the HPLC Fingerprint and Triple-Q-TOF-MS/MS Combined with Quantitative Analysis of 12 Representative Components - Jing Xu; Rongrong Zhou; Lin Luo; Ying Dai; Yaru Feng; Zhihua Dou (Journal of Analytical Methods in Chemistry)
In this study, quality evaluation (QE) of 40 batches of decoction pieces of Gardeniae Fructus (GF) produced by different manufacturers of herbal pieces was performed by qualitative analysis of the HPLC fingerprint and ultra-fast liquid chromatography (UFLC)-triple-Q-TOF-MS/MS combined with quantitative analysis of multiple components, which we established previously for QE of traditional medicine. First, HPLC fingerprints of 40 samples were determined, and the common peaks in the reference fingerprint were assigned. Second, the components of the common peaks in the HPLC fingerprints were identified by UFLC-triple-Q-TOF-MS/MS. Finally, the contents of the components confirmed by reference substances were measured. The results showed that there were 28 common peaks in the HPLC fingerprints of 40 samples. The components of these 28 common peaks were identified as 13 iridoids, 4 crocins, 7 monocyclic monoterpenoids, 3 organic acids, and 1 flavonoid. Of these, a total of 12 components, including 7 iridoids of geniposide, shanzhiside, geniposidic acid, deacetyl asperulosidic acid methyl ester, gardenoside, scandoside methyl ester, and genipin gentiobioside, 2 crocins such as crocin I and crocin II, 1 monocyclic monoterpenoid of jasminoside B, 1 organic acid of chlorogenic acid, and 1 flavonoid of rutin, were unambiguously identified by comparison with reference substances. There were certain differences in the contents of these 12 components among 40 samples. The geniposide content ranged from 37.917 to 72.216 mg/g, and the total content of the 7 iridoids ranged from 59.931 to 94.314 mg/g.